ANALISIS DAMPAK TINGKAT PENGANGGURAN TERBUKA TERHADAP KEMISKINAN MENURUT KABUPATEN DAN KOTA SELAMA PANDEMI COVID-19 DI PROVINSI BANTEN - Devira Dieda Genesia Azzahra; Windy Riqul Aini; Deris Desmawan (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
The purpose of this study is to determine poverty is affected by the open unemployment rate during the COVID-19 pandemic. The first COVID-19 case that entered Indonesia since March 2, 2020 had an impact on various aspects, including increasing the unemployment rate. Layoffs and the difficulty of finding work during the pandemic have led to an increase in open unemployment. Between 2019 and 2021, the number of poor people in the Regency or City of Banten Province is taken as the population. Panel data regression was used in this study for testing and quantitative methods. Based on the results of our research, the poverty rate in cities and districts in Banten Province is not significantly affected by the open unemployment rate.